Pengembangan Media Edukasi Berbasis Progressive Web Apps (Wiyata Care) terhadap Kepatuhan Konsumsi Tablet Tambah Darah dan Peningkatan Kadar Feritin Remaja Putri - Rahmadhani, Aufi; Isnawati, Muflihah; Supriyana, Supriyana (Journal of Telenursing (JOTING), 2024)
This study aims to prove the effect of educational media based on Progressive Web Apps in increasing compliance in consuming TTD and ferritin levels in young women. . The research method used Research and Development (R&D)with develop educational media based on Progressive Web Apps. The results showed Educational media based on Progressive Web Apps (Wiyata Care) has proven to be effective in increasing knowledge, attitudes, compliance with TTD consumption, and ferritin levels in adolescent girls. The Conclusion, The use of educational media based on Progressive Web Apps (Wiyata Care) and compliance in consuming Blood Supplement Tablets are effective in increasing ferritin levels in young women. Keywords : Ferritin, Educational Media, Young Women, TTD.